2013
DOI: 10.7205/milmed-d-12-00426
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Case Series: Treatment of PTSD With Transcendental Meditation in Active Duty Military Personnel

Abstract: Active duty U.S. Army Service Members previously diagnosed with post-traumatic stress disorder (PTSD) were selected from review of patient records in the Traumatic Brain Injury Clinic at the Department of Defense Eisenhower Army Medical Center at Fort Gordon in Augusta, Georgia. Patients agreed to practice the Transcendental Meditation (TM) technique for 20 minutes twice a day for the duration of a 2-month follow-up period. Three cases are presented with results that show the feasibility of providing TM traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…10 A systematic review of 14 randomized clinical trials examining anxiety show TM to be more effective than usual care with the greatest effects on those with high anxiety. 15 A review of meditation studies also supports the safety and potential efficacy of meditative practices as treatments for medical illness, particularly in nonpsychotic mood and anxiety disorders. 16 Preliminary findings for reducing PTSD symptomatology through TM suggested the worth of this intervention to practitioners in the military health care community.…”
Section: Introductionmentioning
confidence: 93%
“…10 A systematic review of 14 randomized clinical trials examining anxiety show TM to be more effective than usual care with the greatest effects on those with high anxiety. 15 A review of meditation studies also supports the safety and potential efficacy of meditative practices as treatments for medical illness, particularly in nonpsychotic mood and anxiety disorders. 16 Preliminary findings for reducing PTSD symptomatology through TM suggested the worth of this intervention to practitioners in the military health care community.…”
Section: Introductionmentioning
confidence: 93%
“…Six studies investigated mantra-based meditation: two RCTs (Bormann, Thorp, Wetherell, & Golshan, 2008;Bormann, Thorp, Wetherell, Golshan, & Lang, 2013); one case-controlled study (Rees, Travis, Shapiro, & Chant, 2013); and three uncontrolled studies (Barnes, Rigg, & Williams, 2013;Rees, Travis, Shapiro, & Chant, 2014;Rosenthal, Grosswald, Ross, & Rosenthal, 2011). One large (N = 146), good-quality RCT found that both MBM combined with treatment as usual (TAU; medication and case management), and TAU alone reduced PTSD symptoms, with greater reductions in the intervention group (Bormann et al, 2013).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Thus, it is restricted to 10 works only. Future empirical research is recommended in order to inspect how meditation can benefit quality of work life and organizational competitiveness among diverse professions, for example, among legal professionals (Halpern, ), military and soldiers (Barnes, Rigg, & Williams, ; Rees, ; Seppala et al, ), nurses (Ando, Natsume, Kukihara, Shibata, & Ito, ; Cohen‐Katz et al, ), social workers (Berceli & Napoli, ), and teachers (Anderson, Levinson, Barker, & Kiewra, ; Gold et al, ).…”
Section: Analyses and Discussionmentioning
confidence: 99%